ARCHITECTURES OF EARTH IN CALABRIA - Pelaia, Ettore (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
The thesis has been done on the town of Lamezia Terme and it is aimed at the recovery and identification of the local construction technique of this area. For this purpose, the research integrated the study of geometric significance, building materials and their degradation analysis. Nowadays, there has been a loss of the empirical knowledge, handed down for centuries. This research aimed to collect and identify some of this knowledge through interviews with the elderly and the masons, who know the local building construction. The research had firstly begun with the identification of building types on an urban scale. Then, it evolved within the investigated area, to the scale of special technological features with specific characteristics. At Lametina region, it is clear that these constructions built in raw earth, reached 5-6 floors above the ground. During the investigation, from the researched archives, it was concluded that the area of the historical buildings was built after 1783. Therefore, it should have inside of the masonry a wooden structure called “Casa Baraccata”. This is an appropriate technology similar to the “Gaiola Pombalina” used in Lisbon, after the earthquake of 1755. It consists in a bearing structure formed by three-dimensional beams and pillars in wood, made through (solid connection of) joints and nails. However, to preserve the wooden structure from decay, the structure was concealed within the masonry, which makes it difficult to be identified. The earthen raw walls have a significant thickness at the base (over 1m) and a tapering of approximately 20cm in every floor above. The walls of the top floor have a consistent thickness of about 30cm obtained by laying the bricks placed above. Another special feature of the area is the “Muratura Civata” (the outer wall made with small pebble stones and fragments of brick earthenware), a wall built with a lot of care. Whilst this is a “not finished” parietal; it is intended to protect the earth masonry from the atmospheric agents, which implies the use of a layer of earthen plaster.